Gendered Justice in China: Victim–Offender Mediation as the “Different Voice” of Female Judges - Wei, Shuai (International journal of offender therapy and comparative criminology, 2021)
Attempts to uncover the “different voice” of female judges through testing the statistical significance of judges’ gender in decision making have offered inconsistent results. Meanwhile, a proliferation of research suggests that such “voice” might be detected through qualitative analysis. Existing findings indicate that when female judges have discretionary power regarding case management, they will typically foster a process of settlement. Based on this information, I conducted eight months of fieldwork in China and observed 68 victim-offender mediations in four district courts. I found that the criminal division is widely perceived as a masculine setting, and female judges are accustomed to employing mediation as a preferred dispute resolution method to facilitate reconciliation between the two parties and seek civil compensation for victims. Such judicial behavior is a result of propaganda from the Supreme People’s Court and a reflection of female judges’ life and work experience. By contrast, a neglect of mediation among male judges can be identified in the same workplace. The belief that mediation is feminine and time-consuming contributes to this neglect. In addition, rape lawsuits are an exception for mediation. This explorative research not only represents one of the first efforts to reveal a “different voice” in the Chinese criminal justice system but points out a direction of research for studying the judicial behaviors of female judges worldwide.